Reflections of Asabiyyah Effect on Social Differentiation in Social Media: The Case of the July 15th Military Coup Attempt - Mustafa Sami Mencet; Onur Ertürk (Türkiye İletişim Araştırmaları Dergisi)
During the July 15th Coup Attempt in Turkey, many firsts were experienced. The Grand National Assemblyof Turkey and other state buildings were bombed by Turkish warplanes led by putschist pilots, the civilianswere fusilladed intensively and their resistance was strong and uncompromising. Yet, the media subordinateto the putschists in previous coup attempts played a crucial role in the failure of the putschists in this coupattempt. Just after the President’s call to civilians for resistance in the squares, many people, who wereorganized in the social media platforms, shielded themselves against soldiers and tanks immediately, butthe soldiers of junta could manage to kill 173 civilians. Meanwhile, another part of the society kept theirsilence and went to ATMs or markets in fear of a probable war. When the activities in the social mediawithin the process of the coup attempt are considered, it can be figured out that both parts of the societywere influenced by the social media contents and that they acted accordingly. An in-depth analysis ofthe elements that affect the perception, and reactions within these two different segments of the society,attitude-development and action-taking of these two parts is vital for the prevention of such attempts whichhave the power to directly influence the well-being of the country and the peace of the society. For thispurpose, in this study, social media activities and the reactance of the masses pre – and intra-coup attemptare analyzed. Two hashtags and two visual contents representing the different reflections of the processof the 15th of July Coup Attempt in the social media are analyzed through Roland Barthes’s SemiologicalDenotation/Connotation Model, and the role of the media in the assumption of different attitudes of themasses are examined by scrutinizing the different attitudes of both pro – and against-government partiesand the collective actions through the Asabiyyah theory of Ibn Khaldun. Findings summarizes factorsthat are threating the social peace and reinforcing discrimination; and furthermore, they show why it isimportant to adopt the Asabiyyah theory to understand such social events.